Business taxation and wages: Evidence from individual panel data - Thomas K. Bauer; Tanja Kasten; Lars-H. R. Siemers (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2012)
Empirical evidence on the degree of business-tax shifting to employees via the wage level is highly controversial and rare. It remains open to which extent the tax burden is shifted, whether there are differences for tax increases and decreases, or whether there exists some treatment heterogeneity, that drive the respective results. Using a large administrative panel data set, we exploit the regional variation of the German business income taxation to adress these issues. Our results suggest an elasticity of wages with respect to business taxes that ranges between -0.28 to -0.46, once we control for invariant unobserved regional and individual characteristics. Workers with low bargaining power, e.g., low-skilled, are affected most from business tax shifting, indicating that business-tax incidence involves distributional effects. Finally, we find evidence for an asymmetric tax incidence.
Keywords: H22; H25; J31; J38; 330; tax incidence; profit taxation; wages; asymmetric effects; Unternehmensbesteuerung; Körperschaftsteuer; Steuerinzidenz; Lohnniveau; Schätzung; Deutschland